Support mechanisms for Canada's cultural and creative sectors during COVID-19 - Charlie Wall-Andrews; Emma Walker; Wendy Cukier (Journal of Risk and Financial Management, 2021)
The cultural and creative industries enhance the quality of life for Canadians and visitors to Canada. However, definitions of the sector vary, presenting challenges for researchers and policymakers. Government data shows that the pandemic job and revenue loss were disproportionate in the arts. The Canadian government created a range of financial tools (grants and subsidies) to support the sector during the Pandemic. This paper analyzes these financial instruments created in response to the Pandemic. This paper offers a case study on how government can support the economic and social success of the creative and cultural sector (CCS) in Canada and avoid the risk of the cultural ecosystem collapsing. In addition, the key findings may be helpful in other industries and markets when exploring ways to support the cultural and creative sectors, which are vital components of domestic and tourism activity.
Keywords: 330; cultural investment; stimulate tourism; pandemic recovery; Canada; public policy; grants and financial instruments; arts management; cultural policy